Pain in children and adolescents - Olga V. Kotova; Irina V. Borodulina (LLC "MEDIAFORMAT", 2024)
Pain is represented in the child and adolescent population all over the world, and many young adults have chronic pain. Chronic pain is accompanied by the lifestyle and functioning alteration, as well as by the development of depression and anxiety symptoms. The global prevalence of chronic pain among children varies between 20 and 40%, about 8% of children report frequent severe pain, and 5% of children and adolescents become disabled due to pain. Headache (HA) is a common complaint of children and adolescents: by the age of 3 years complaints of HA are reported in 3-8% of children, by the age of 5 years in 19.5%, by the age of 7 years in 37-51.5% of children. The prevalence of HA, regardless of the subtype, is almost the same in girls and boys under the age of 12 years. The main HA subtypes that occur in pediatric practice are as follows: migraine (with or without aura), tension-type HA, cluster HA. Pain, including HA, is often associated with mental disorders in children and adolescents. Thus, the study focused on assessing the relationship between HA and mental disorder in the representative sample (10,123 people) confirmed the association between HA, especially migraine, and mental disorders in adolescents. The strongest associations were reported between migraine and mood disorders and anxiety, behavioral disorders, and substance use. Young adults with HA, especially migraine, more often suffered from multiple mental disorders. The paper presents a clinical case of the 10-year-old girl with the autism spectrum disorder and the combination of migraine without aura and depressive disorder.